Pembuatan Sistem Kendali Numerik untuk Pengerak Sistem Inspeksi Visi - Sulaksana, Bambang; Burhanuddin, Yanuar; Sadnowo R, Ageng (Jurnal Ilmiah Teknik Mesin FEMA, 2014)
Commonreasons for implementing automated vision inspection system has been discussed by previous researchers. Many advantages when compared to automated vision inspection of human visual inspection. Automated vision inspection system can work tirelessly, and has accuracy and consistent quality control. Vision inspection system can detect defects that are hard to find by the human visual. Without tools and can operate faster than the human visual. This research will use the software as mach3 CNC control system controls the computer, as the driving bipolar stepper motors, and motor driver IC that is used as a controller L297 and L298 stepper motors. Measuring instruments that are used for data retrieval using calipers. Testing is done by measuring the displacement of the desk and then compare the measured values with values that ruled on the computer simulation of translational motion as far as    1 cm, 2 cm, 3 cm, 4 cm, 5 cm, and 6 cm.From the testing that has been done on each axis movement values obtained average error as follows: on the x-axis value obtained the largest average error was 3%. Then the z axis has an average value of the largest error is 8.4%. Value of the compensation amount given step is 2 times the amount of an ideal step.Keywords: Software Mach3 CNC,  Driver L297 &  L298, Stepper Motor - bipolar.